Papers and recommendations on the workshop on food and nutrition security in Jamaica in the 1980's and beyond - Leslie, Kenneth A., ed. (National Food and Nutrition Coordinating Committee ofJamaica KingstonJM, 1987)
The principal objectives of the workshop were to examine the issues involved in achieving adequate food and nutrition security at the national and household levels, and to develop policy and programme recommendations to facilitate their achievement. Contains main technical papers delivered at the workshop and recommendations on policies and programmes which emerged from the discussions.